Localization and Function of GABA Transporters GAT-1 and GAT-3 in the Basal Ganglia - Jin, Xiaotao; Galvan, Adriana; Wichman, Thomas; Smith, Yoland (Frontiers in Systems Neuroscience, 2011)
GABA-transporter type 1 and 3 (GAT-1 and GAT-3, respectively) are the two main subtypes of GATs responsible for the regulation of extracellular GABA levels in the central nervous system. These transporters are widely expressed in neuronal (mainly GAT-1) and glial (mainly GAT-3) elements throughout the brain, but most data obtained so far relate to their role in the regulation of GABAA receptor-mediated postsynaptic tonic and phasic inhibition in the hippocampus, cerebral cortex and cerebellum. Taking into consideration the key role of GABAergic transmission within basal ganglia networks, and the importance for these systems to be properly balanced to mediate normal basal ganglia function, we analyzed in detail the localization and function of GAT-1 and GAT-3 in the globus pallidus of normal and parkinsonian animals, in order to further understand the substrate and possible mechanisms by which GABA transporters may regulate basal ganglia outflow, and may become relevant targets for new therapeutic approaches for the treatment of basal ganglia-related disorders. In this review, we describe the general features of GATs in the basal ganglia, and give a detailed account of recent evidence that GAT-1 and GAT-3 regulation can have a major impact on the firing rate and pattern of basal ganglia neurons through pre- and post-synaptic GABAA- and GABAB- receptor-mediated effects.